Genetic characterization of cassava (Manihot esculenta Crantz) traits using argo-morphological characters - Iyanda, S.A. (University of Lagos, 2021)
Cassava (Manihot esculenta Crantz) is an important crop in Nigeria where leaves and tubers are eaten. However, its genetic variability remains unexplored in Nigeria. Local varieties are precious genetic resources because of their diversity. Mastery of this diversity is an important basis for crop improvement through plant breeding programs. Local cassava accessions (99) were collected mainly from the international institute of tropical agriculture (IITA), Ibadan, Southwestern part of Nigeria. These accessions have been planted with the objective to characterize them, based on morphological agro-morphological traits, and parameters were recorded at three, six, nine and twelve months after planting. The experiment was carried out in experimental station of IITA, and sixty-two (62) morphological were used. Significant differences (p<0.05) were observed for all the 62 analysed morphological traits. A total of twenty-one principal component analysis (PCA) in the trait sets accounted for eigen value range of 7.55 to 1.01 and a cumulative percentage variance of 83.95% to 11.45% of the total genetic variation. The Principal Component Analysis reveals traits with positive high dispersion of the accessions. On the cluster analysis, the accessions were classified in four groups. The matrices of genetic dissimilarity were used in the construction of dendrograms using the UPGMA method. We observed a high variation of agronomical descriptors which were capable to separate the accessions into four distinct clusters. This work showed the variation in agronomic traits existing among cassava accessions in IITA, Ibadan, Nigeria that could be exploited to enhance cassava breeding programs.